x ao quadrado+6x+9=0
orion77:
x' = -3 e x'' = -3
Soluções para a tarefa
Respondido por
15
Delta = b² - 4.a.c
Delta = 6² - 4.1.9
Delta = 0
X' = (-6 + raiz quadrada de Delta)/2*1
X' = -3
X'' = (-6 - raiz quadrada de Delta)/2*1
X''= -3
Ou seja, x = -3
Só usar Baskhra
Abçs
Delta = 6² - 4.1.9
Delta = 0
X' = (-6 + raiz quadrada de Delta)/2*1
X' = -3
X'' = (-6 - raiz quadrada de Delta)/2*1
X''= -3
Ou seja, x = -3
Só usar Baskhra
Abçs
Respondido por
3
x²+6x+9=0
(6)²-4.1.9
36-36=0
(6)²-4.1.9
36-36=0
Perguntas interessantes
História,
9 meses atrás
Matemática,
9 meses atrás
História,
9 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Ed. Técnica,
1 ano atrás